Assessing House Prices in Canada - Andrle, Michal (IMF Working Papers; Working Paper ;, 2019)
This paper assesses house prices in 11 Canadian Census Metropolitan Areas (CMA) using the borrowing-capacity and the net-present-value approaches. The results indicate that by the end of 2018, house prices in most metropolitan areas are aligned with macroeconomic fundamentals. However, in Hamilton, Toronto, and Vancouver house prices have increased beyond the values implied by the fundamentals.